1983
DOI: 10.1161/01.res.52.3.335
|View full text |Cite
|
Sign up to set email alerts
|

Overperfusion, hypoxia, and increased pressure cause only hydrostatic pulmonary edema in anesthetized sheep.

Abstract: Overperfusion (high pressure and flow through a restricted microvascular bed) has been suggested as the mechanism for both microembolic and high altitude pulmonary edema. In eighteen anesthetized, ventilated sheep, we measured pulmonary hemodynamics, lung lymph flow, and lymph:plasma protein concentration ratio. After a 2-hour stable baseline, we resected 65% of lung mass (right lung and left upper lobe) and gave whole blood transfusions to maintain cardiac output. During overperfusion of the left lower lobe, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
3

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 20 publications
0
16
0
3
Order By: Relevance
“…There was a mean increase of 7 cm H20 in the calculated pulmonary microvascular pressure in the oleic acid studies, based primarily on a rise in pulmonary arterial pressure. Therefore, we studied two sheep in which left atrial pressure was increased by 7 cm H20 with a left atrial balloon, as we have done before (14), and then instilled serum into one lower lobe. The same variables were measured as in the other experiments.…”
Section: Specific Protocolsmentioning
confidence: 99%
“…There was a mean increase of 7 cm H20 in the calculated pulmonary microvascular pressure in the oleic acid studies, based primarily on a rise in pulmonary arterial pressure. Therefore, we studied two sheep in which left atrial pressure was increased by 7 cm H20 with a left atrial balloon, as we have done before (14), and then instilled serum into one lower lobe. The same variables were measured as in the other experiments.…”
Section: Specific Protocolsmentioning
confidence: 99%
“…Elegant studies using sheep have previously demonstrated that acute increases in PBF or pressure led to increased capillary filtration of protein-poor fluid and augmented clearance of lymphatic fluid (12,19,42,44,50). However, infants born with congenital cardiac defects often live with increased PBF for months or years before their defects are surgically corrected, and it remains unknown what effect this chronically increased PBF has on the function and structure of the pulmonary lymphatic system.…”
mentioning
confidence: 99%
“…In contrast to our results with preterm lambs and a PDA, L:P increased as lymph flow increased in lambs with pulmonary oxygen toxicity. In studies performed with adult sheep that had almost two thirds of their total lung mass resected, Landolt et al (6) did not detect any evidence of increased lung vascular permeability, despite the fact that the entire cardiac output of these sheep flowed through only a small fraction of the pulmonary vascular bed. Thus, we think that increased blood flow to the lungs through a PDA, even in relatively small lungs of preterm lambs, does not cause an increase in pulmonary vascular protein permeability.…”
Section: Discussionmentioning
confidence: 96%
“…PC was calculated using Gaar's equation (5) in the form PC = PLvED + 0.4 (PpA -PLVED). This equation correlates well with capillary pressure as measured by arterial occlusion (5) and has been used in experiments with pulmonary overperfusion (6). Although the assumptions underlying the partition values chosen in this equation may not hold in conditions of very high pulmonary flow, we are using PC as an index of filtration pressure.…”
Section: Abbreviationsmentioning
confidence: 87%